2001
DOI: 10.4049/jimmunol.167.10.5904
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nitric Oxide Synthase Initiates Relapsing Remitting Experimental Autoimmune Encephalomyelitis in Rats, Yet Nitric Oxide Appears to be Essential for Clinical Expression of Disease

Abstract: Myelin basic protein-CFA-induced experimental autoimmune encephalomyelitis (EAE) in Lewis rats is an acute monophasic disease from which animals recover. In this model, spontaneous relapses do not occur and rats develop a resistance to further active reinduction of disease. Previously, we reported that oral administration of the NO synthase inhibitor N-methyl-l-arginine acetate (l-NMA) to recovered rats precipitated a second episode of disease in 100% of animals. Further studies now show that this second clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
6
26
0
Order By: Relevance
“…48,49 Several studies have therefore proposed a dual role for NO, showing that iNOS activity is destructive in the acute phase of disease but protective in the progressive phase. 50,51 The dual effects of NO in disease pathogenesis are well demonstrated in NOS2A knockout mice infected with Toxoplasma gondi. 52 During acute infection, knockout mice survived because of the removal of an intense inflammatory response that killed most normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Several studies have therefore proposed a dual role for NO, showing that iNOS activity is destructive in the acute phase of disease but protective in the progressive phase. 50,51 The dual effects of NO in disease pathogenesis are well demonstrated in NOS2A knockout mice infected with Toxoplasma gondi. 52 During acute infection, knockout mice survived because of the removal of an intense inflammatory response that killed most normal mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although different events, including alteration of cytokine production, changes in T cell sensitivity to proapoptotic signals, and/or the production of suppressor molecules (20,21), may participate in the immunosuppression of Tg mice, the final common pathway appears to be macrophage activation of iNOS/NO, as demonstrated by studies ex vivo and in vitro, using NOS inhibitors, NO scavengers, or NO donors. In addition, the ability of L-NIL treatment in vivo to sharply increase MOG-reactive LNC and spleen cell proliferation and revert the EAE resistance of GR-deficient mice further supports the participation of iNOS/NO in counteracting MOG reactive cell expansion during the early induction phase of EAE (46,55). Several endogenous and exogenous molecules can induce (LPS, IFN-␥, TNF-␣, and IL-1␤) or repress (TGF-␣, IL-4, IL-8, IL-10, corticosteroids, and estrogens) iNOS activity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, peritoneal exudate from IFN-␥ ϩ/ϩ -resistant mice produced high levels of NO and down-regulated Ag-driven cell proliferation of IFN ␥ Ϫ/Ϫ mice (46). The down-regulatory effect of NO in primary EAE has been previously suggested to involve inhibition of T cell proliferation as well as inhibition of cell adhesion and migration (55). Such modulation may be dependent on the known functions of iNOS/NO, such as suppression of cytokine production, scavenging of superoxide, and/or apoptosis of macrophages or (encephalitogenic) T cells (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that the mechanism of EAE inhibition in iron-deficient mice involves the delivery and metabolism of iron for optimal CD4 þ T-cell development (Grant et al, 2003). Some investigators have shown iNOS inhibition as well as NO scavenging to suppress EAE (Cross et al, 1994;Zhao et al, 1996;Hooper et al, 1997;Jolivalt et al, 2003), whereas others have shown iNOS inhibition (O'Brien et al, 1999(O'Brien et al, , 2001 or NO donor (Xu et al, 2001) to aggravate or ameliorate EAE, thus not clarifying the exact role for NO .…”
Section: Oxidative Stress and Antioxidantsmentioning
confidence: 99%